2000
DOI: 10.1046/j.1365-2044.2000.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a pain‐free venepuncture

Abstract: SummaryA randomised, prospective trial was conducted to assess the efficacy of various means of alleviating the pain of subcutaneous lidocaine infiltration. One hundred and twenty-two patients were randomly allocated to different groups to receive buffered lidocaine 1%, warmed lidocaine 1% or infiltration by the counter-irritation technique. A visual analogue pain score was recorded at different stages of cannulation and results showed that pain scores were significantly lower in the group receiving buffered l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Whereas a multitude of investigators have championed other techniques such as altering the rate of infiltration [14,36], distraction methods, buffering [16-19, 37, 38] and warming the anaesthetic agents [39][40][41][42] in a variety of settings, there is no clear consensus as to the best method to reduce infiltrative pain, as no-one has sought to combine all these techniques in a prospective randomised study. Some studies have demonstrated that warm buffered anaesthetic agents induce less pain during infiltration than either warmed or buffered agents used in isolation, and that buffering solutions is preferable to warming the anaesthetic agents [9,12,13]. However, it is difficult to make comparisons between these studies as considerable heterogeneity exists in the volume of infiltrate, the technique and anatomical location of infiltration, and the method of warming and buffering procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas a multitude of investigators have championed other techniques such as altering the rate of infiltration [14,36], distraction methods, buffering [16-19, 37, 38] and warming the anaesthetic agents [39][40][41][42] in a variety of settings, there is no clear consensus as to the best method to reduce infiltrative pain, as no-one has sought to combine all these techniques in a prospective randomised study. Some studies have demonstrated that warm buffered anaesthetic agents induce less pain during infiltration than either warmed or buffered agents used in isolation, and that buffering solutions is preferable to warming the anaesthetic agents [9,12,13]. However, it is difficult to make comparisons between these studies as considerable heterogeneity exists in the volume of infiltrate, the technique and anatomical location of infiltration, and the method of warming and buffering procedures.…”
Section: Discussionmentioning
confidence: 99%
“…These include application of topical analgesics such as amethocaine [10], distraction techniques [11], counter irritation [12], warming the anaesthetic agents [13], varying rates of infiltration [14] and buffering the local anaesthesia [9,[15][16][17][18][19].…”
mentioning
confidence: 99%
“…The pain of local anaesthetic injection is only 1-2/10 in severity, and thereafter the procedure of venous cannulation or ABG sampling should be virtually painless. 1,6,7 If the pain of initial injection is deemed an issue, various ways to lessen it have been suggested including buffering with sodium bicarbonate to reduce acidity, 12 warming of the solution, 13 and injection via a 27G needle of the sort used for subcutaneous insulin.…”
Section: Discussionmentioning
confidence: 99%
“…6(1), 399-405 400 process. 6 Various methods are used including topical ethyl chloride, eutectic mixture of local anaesthetic (EMLA), intradermal or subcutaneous (SC) Lignocaine (lidocaine). 8 All have been shown to significantly reduce cannulation pain.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…1 Local anaesthetic to relieve the pain of intravenous cannulation is widely used in paediatric and some anaesthetic practice. [1][2][3][4][5][6][7] The procedure is associated with pain, anxiety and frustration in patients and changes in hemodynamic parameters. Studies have shown that the use of local anesthesia decreases the pain of I /V cannulation.…”
Section: Introduction:-mentioning
confidence: 99%